Pengaruh Bunga Telang (Clitoria Ternatea L.) dalam Pemurnian Minyak Jelantah dari Hasil Penggorengan KFC Jalanan - Nur, Alfin; Zaini, Halim; Irwan, Irwan (Jurnal Teknologi, 2024)
Butterfly pea flower is a plant that is very familiar to Indonesian people, this flower has a bright purple color and contains antioxidants which can reduce levels of free fatty acids in used cooking oil. The purpose of this study was to determine the effect of variations of time on the refining of used cooking oil. The study conducted by analyzed the reduction of free fatty acid, different mass of  butterfly pea flower. The results showed that, the initial free fatty acid data was 6.13% and the final free fatty acid number was 1.37%, the lowest moisture content test was 0.4%, the highest antioxidant test result was 89.51%, the lowest peroxide number test was 4 meq O2/kg and the organoleptic test was 3.75. Based on these data, it can be concluded that this research was declared successful in processing of used cooking oil even though it did not meet the quality standards of the Indonesian National Standard (SNI).